Evaluation of Hearing in Patients With Rheumatoid Arthritis Compared With Controls - Volkan Gökçe, Assist. Prof. Zafer; Öztürk, Sidar; Paltura, Ceki (ENT Updates, 2019)
Objective: To demonstrate the effects of rheumatoid arthritis (RA) on hearing with audiometric and tympanometric measurements, and to reveal its relationship with the disease in comparison with healthy volunteers. Methods: The study included 30 RA patients and 30 healthy controls. Demographic findings such as age, height, weight, onset of complaint (year), time elapsed since diagnosis, previous surgery, accompanying systemic disease, drugs used, family history, habits of smoking and alcohol use were questioned for both groups. Tympanometry, pure voice audiometry and otoacoustic Emission tests were performed. Results: The hearing thresholds in the airway conduction in RA group were significantly higher in all frequencies (0.25-6 kHz) than in the control group. When bone conduction hearing thresholds were compared, RA group was more affected at only 4 kHz and left ear (p=0.006). When air-bone conduction differences (AB-gap) were examined, the differences in the RA group at 0.5, 1 and 4 kHz were statistically significant. When tympanometry and acoustic reflex measurement results were evaluated, there was no statistically significant difference between groups. In the transient OAE test, 3 (10%) patients were in the RA and 2 (6.6%) patients in the control group (p=0.064). Conclusion: Conductive hearing loss was significantly more frequent in patients with RA than in healthy individuals, whereas bone conduction was affected partially at high frequencies; whereas stapes reflex, compliance and pressure values were not significantly affected.